The effect of turbo-charging and intercoolingon emissionsgeneration [i.e. intercooling on emissions generation] and durability of a diesel engine - Emslie, Lovell Donald (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScEng)--University of Stellenbosch, 2001.